Perspectives on Auditory Research - Popper, Arthur N.; Fay, Richard R. (Springer Handbook of Auditory Research, 2014)
Perspectives on Auditory Research is the 50th volume in the 21-year history of the Springer Handbook of Auditory Research (SHAR).  SHAR was originally conceived as having perhaps eight volumes on the fundamental and more mature topics of auditory neuroscience. The vision in developing SHAR was to ask authors to discuss the major concepts of the authors' discipline. In other words, to have chapters that present the most expert conceptual overview of a particular field. In contrast to the past 49 volumes, volume 50 consists of essays by senior colleagues that focus on their contributions to auditory neuroscience in the past, on their views of the state of the field, and on their thoughts on the future of their field including the outstanding questions that are still unanswered. The chapters are written in the first person, and some provide "autobiographical" information. The aim was to have senior scholars think about their discipline and even their careers and write whatever they wanted.  The result is a highly diverse series of chapters, all of which might be different in style and approach and which will be interesting and 'fun" for the reader. The hope is that readers browse the book for the "fun of it" rather than look for specific topics.              About the Editors: Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. Richard R. Fay is Distinguished Research Professor of Psychology at Loyola University Chicago.   About the Series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.